2018
DOI: 10.5944/openpraxis.10.4.892
|View full text |Cite
|
Sign up to set email alerts
|

Open Textbooks in an Introductory Sociology Course in Canada: Student Views and Completion Rates

Abstract: Open educational resources (OER), including open textbooks, are free, adaptable learning resources. The integration of these materials in place of commercial textbooks allows for considerable financial savings for students and creates opportunities for more active and engaged learning. The growing interest in the use of OER at a Western Canadian university led to the chance to survey students for their feedback on using OER instead of traditional commercial textbooks. This paper focuses on the views of student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…74% of students who used the CT said that they were satisfied versus 57% of students who used the OER Clinton (2018) 458 N/A Students rated CT and OER to be of equal quality Griffiths et al (2018) 2350 34% of students said OER were the same quality as CT, with 29% and 30% reporting respectively that they were slightly higher or much higher. 2% and 5% respectively said they were much or slightly lower quality Carpenter-Horning (2018) 227 N/A Students who used OER reported significantly higher levels of perceived cognitive learning in the course, relative to those using CT Hunsicker-Walburn et al (2018) 90 N/A 33% of these students said the quality of OER were better than CT, 54% said they were the same with 12% stating OER were worse Ross et al (2018) 129 46% said the OER were excellent relative to other textbooks, 27%, above average, 19% average, 6% below average, and 2% very poor Total 10,807…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…74% of students who used the CT said that they were satisfied versus 57% of students who used the OER Clinton (2018) 458 N/A Students rated CT and OER to be of equal quality Griffiths et al (2018) 2350 34% of students said OER were the same quality as CT, with 29% and 30% reporting respectively that they were slightly higher or much higher. 2% and 5% respectively said they were much or slightly lower quality Carpenter-Horning (2018) 227 N/A Students who used OER reported significantly higher levels of perceived cognitive learning in the course, relative to those using CT Hunsicker-Walburn et al (2018) 90 N/A 33% of these students said the quality of OER were better than CT, 54% said they were the same with 12% stating OER were worse Ross et al (2018) 129 46% said the OER were excellent relative to other textbooks, 27%, above average, 19% average, 6% below average, and 2% very poor Total 10,807…”
Section: Discussionmentioning
confidence: 99%
“…They conclude that their "findings do not support the notion that OERs represent a dramatic improvement over commercial texts, nor do they indicate that students perform substantially worse when using open content texts either" (p. 563). Ross et al (2018) studied the use of the OpenStax Sociology textbook in an introductory Sociology course at the University of Saskatchewan. One instructor taught a sociology course with a CT in the 2015-2016 school year (n = 330), and then used an OpenStax textbook in the fall of 2016 (n = 404).…”
Section: Studies That Accounted For Teacher But Not Student Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies have shown OER to positively influence student grades (Winitzky-Stephens & Pickavance 2017), buy-in (Sapire & Reed 2011), accessibility (Cooney 2017), study habits (Jhangiani & Jhangiani 2017), sense of perspective (Choi & Carpenter 2017), and so on. Consequently, Ross, Hendricks, and Mowat (2018) found 73% of students rated their open textbooks as "excellent" or "above average," and Bliss et al, (2013) found a staggering 89% of educators and 94% of students rated their open course materials as being equal or better in quality than the traditional textbooks they previously used.…”
Section: Literaturementioning
confidence: 99%
“…In Canada, the province-wide British Columbia Open Textbook project is supporting educators to create a range of open textbooks in core subjects (BCcampus, n.d.), while eCampusOntario is funding the development of curriculum-aligned open textbooks in the province (eCampusOntario, n.d.). Jhangiani and Jhangiani (2017) were the first to report on Canadian student experiences of open textbooks, and there is a growing body of open textbook impact research in the Canadian context (e.g., see Hendricks et al, 2017;Jhangiani et al, 2018;Jhangiani et al, 2016;Ross et al, 2018).…”
Section: The North American Contextmentioning
confidence: 99%